OUR HUSBAND AND CHILDREN ARE NOT ACKNOWLEDGED: Endogamy, Gendered Power, and Child Issues in the ‘Alawiyyīn Marriage in Indonesia - Rahmaniah, Syarifah Ema; Taufik, Egi Tanadi (JOURNAL OF INDONESIAN ISLAM, 2024)
This paper analyzes the endogamous marriage practices among the ‘Alawiyyīn community in Pontianak Indonesia and the problems of gender inequality and child discrimination. This ethnographic research was conducted within eight months in 2021 and 2023. The doctrine of endogamy is actually misogynistic narratives towards the Sharifah women, silent resistance against exogamy, and refusal of half-blood child. The discussion analyzes the phenomenon of Muslim kin marriage within the socio-setting of religious-historical aristocracy and the patriarchal hegemony of the patrilineal community. It also highlights how the ‘Alawiyyins of Pontianak defend the doctrine of endogamy as institutionalized in the concept of kafa’at against exogamy practices among the community. The resistance to endogamy is practiced as a complex negotiation among ‘Alawiyyīn members for normalizing exogamy as they re-internalize and institutionalize the doctrine of kafā’at. Against the dogma, the exogamy marriage directly affects normalizing non-familial marriages among ‘Alawiyyīns, restoring the social status of those performed out-marriage and recognizing their descendants as clan members. However, the insistence of ‘Alawiyyīns in defending their kin marriage doctrine at all-cost makes this counter narrative remain in the sideline at the moment.